Bi8O6 (OH) 4 (SO4) (NO3) 6.H2O compound and crystal, preparation method and application thereof
By introducing NO3- and SO42- groups into nonlinear optical crystals, the Bi8O6(OH)4(SO4)(NO3)6·H2O compound was synthesized, which solved the development challenges based on a single compound system in the prior art, and achieved the preparation of nonlinear optical crystals with strong frequency multiplication effects and high transmittance in the ultraviolet-near infrared region.
Patent Information
- Application Number
- CN202411830566.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-12
Smart Images

Figure CN119841346A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional crystal materials, and in particular relates to a Bi8O6(OH)4(SO4)(NO3)6·H2O compound and its crystal, a preparation method and application in nonlinear optics. Background Art
[0002] Nonlinear optical crystals have a wide range of applications in industry, civil, medical and national defense. The research on nonlinear optical crystals has always been a hot topic in the field of optoelectronic functional crystals. Relying on their frequency conversion performance, they can easily convert mature lasers to other bands, thereby expanding the range of laser wavelengths and meeting the application needs of different fields. With the continuous development of laser technology, the requirements for the performance of nonlinear optical crystals are also constantly increasing, and the exploration of new nonlinear optical crystals is becoming more and more challenging. Anion group theory plays an important guiding role in the exploration of nonlinear optical crystals. From the perspective of compound systems and functional elements, most of the previous development of nonlinear optical crystals came mainly from borates, phosphates, sulfates and other planar triangular π conjugated (BO3) 3- Groups and Tetrahedrons (BO4) 5- 、(PO4) 3- and (SO4) 2- Currently, the strategy based on the combination of functional units, by introducing two or more anionic functional units in the same crystal, has been proven to be an effective way to develop new nonlinear optical crystals. However, the synthesis of compounds with complex functional units is often very challenging. Summary of the invention
[0003] Based on the above background, the present invention provides a compound with the chemical formula Bi8O6(OH)4(SO4)(NO3)6·H2O.
[0004] The present invention also provides a method for preparing the compound with the chemical formula Bi8O6(OH)4(SO4)(NO3)6·H2O, which comprises: mixing a compound containing the Bi element, a compound containing the S element and a compound containing the N element, and subjecting the mixture to a hydrothermal reaction to prepare the compound with the chemical formula Bi8O6(OH)4(SO4)(NO3)6·H2O.
[0005] According to an embodiment of the present invention, the compound containing the Bi element is selected from at least one of Bi2O3, BiF3, Bi(NO3)3·5H2O and BiI3, preferably Bi(NO3)3·5H2O.
[0006] According to an embodiment of the present invention, the compound containing the S element is selected from at least one of H2SO4, (NH4)2SO4, K2SO4 and CaSO4, preferably H2SO4.
[0007] According to an embodiment of the present invention, the compound containing the N element is selected from at least one of LiNO3, NaNO3, KNO3, Ba(NO3)2 and Bi(NO3)3·5H2O, preferably Bi(NO3)3·5H2O. When the compound containing the Bi element and the compound containing the N element are both selected from Bi(NO3)3·5H2O, the addition amount is calculated according to the stoichiometric ratio in the chemical formula, or the addition amount is determined according to the following ratio.
[0008] According to an embodiment of the present invention, in the compound containing Bi element, the compound containing S element and the compound containing N element, the molar ratio of Bi, S and N is n(Bi):n(S):n(N)=(5-20):(1-2):(15-60); preferably (8-16):(1-2):(24-48); exemplified by 8:1:24, 15:2:45 and 10:1:30.
[0009] According to an embodiment of the present invention, the hydrothermal reaction is carried out in a solvent, and the solvent can be selected from an organic solvent or an inorganic solvent, preferably an inorganic solvent, such as a mixture of water and sulfuric acid, exemplified by a deionized aqueous solution of sulfuric acid.
[0010] According to an embodiment of the present invention, the volume ratio of the total mass of the raw materials (i.e. the sum of the masses of the compounds containing the Bi element, the compounds containing the S element, and the compounds containing the N element) to the solvent can be (60-150) g:100 mL, preferably (70-100) g:100 mL; exemplary are 75 g:100 mL, 85 g:100 mL, and 95 g:100 mL.
[0011] According to an embodiment of the present invention, the reaction temperature of the hydrothermal reaction may be 160 to 220° C., preferably 180 to 220° C., for example 180° C., 200° C., 220° C. Further, the heating rate of the hydrothermal reaction may be 10 to 30° C. / h, exemplified by 10° C. / h, 20° C. / h, 30° C. / h.
[0012] According to an embodiment of the present invention, the reaction time of the hydrothermal reaction may be 1 to 3 days, preferably 1 to 2 days, exemplified by 1 day or 2 days.
[0013] According to an embodiment of the present invention, the preparation method further comprises: after the hydrothermal reaction is completed, collecting a compound with a chemical formula of Bi8O6(OH)4(SO4)(NO3)6·H2O from the reaction solution.
[0014] The present invention also provides a nonlinear optical crystal, the chemical structural formula of which is Bi8O6(OH)4(SO4)(NO3)6·H2O, that is, the nonlinear optical crystal is a Bi8O6(OH)4(SO4)(NO3)6·H2O crystal.
[0015] According to an embodiment of the present invention, the nonlinear optical crystal belongs to the orthorhombic system, the space group is Pmn21; the unit cell parameters are α=β=γ=90°, z=8.
[0016] According to an embodiment of the present invention, the nonlinear optical crystal has no center of symmetry.
[0017] According to an embodiment of the present invention, the nonlinear optical crystal has the following Figure 1 The crystal structure shown is composed of [Bi8O 10 (SO4)] blocks the polar cage and free [NO3] - A zero-dimensional crystal structure.
[0018] According to an embodiment of the present invention, the nonlinear optical crystal has the following Figure 2 X-ray diffraction pattern shown.
[0019] According to the embodiment of the present invention, the ultraviolet absorption edge of the nonlinear optical crystal can reach 265nm, the band gap is 4.09eV, and a higher transmittance can be achieved between 0.3 and 2.0μm.
[0020] The present invention also provides a method for preparing the nonlinear optical crystal, characterized in that the method comprises: mixing a compound containing a Bi element, a compound containing an S element, a compound containing an N element and a solvent, and heating and crystallizing the mixture to obtain the nonlinear optical crystal.
[0021] According to an embodiment of the present invention, the selection of the Bi-containing compound, the S-containing compound, the N-containing compound and the solvent are respectively consistent with the selection in the preparation method of the compound with the chemical formula Bi8O6(OH)4(SO4)(NO3)6·H2O.
[0022] According to an embodiment of the present invention, the temperature of the heating crystallization is 160 to 240°C, preferably 180 to 220°C;
[0023] The heating crystallization time is 5 to 15 days, preferably 5 to 12 days, and exemplified by 5 days, 7 days, 10 days, and 15 days.
[0024] According to an embodiment of the present invention, the preparation method further comprises: after the crystallization is completed, cooling, separating and drying the reaction liquid to obtain the nonlinear optical crystal.
[0025] According to an embodiment of the present invention, during the cooling process, the cooling rate is 1-20°C / h, specifically 1-10°C / h, exemplified by 1°C / h, 5°C / h, and 9°C / h.
[0026] According to an embodiment of the present invention, the method for preparing the nonlinear optical crystal specifically comprises the following steps:
[0027] (1) mixing a compound containing a Bi element, a compound containing a S element, a compound containing a N element and a solvent, and heating the mixture to 160 to 240° C. at a rate of 10 to 30° C. / hour for crystallization for 5 to 15 days;
[0028] (2) After the crystallization is completed, the reaction system is cooled to room temperature at a rate of 1 to 20° C. / h, and the nonlinear optical crystal is obtained after separation and drying.
[0029] The present invention also provides the use of the nonlinear optical crystal in optical devices, for example, it can be used in the fields of laser frequency conversion, electro-optic modulation, photorefractive information processing or information storage.
[0030] Preferably, it is used as a frequency doubling device in an all-solid-state laser.
[0031] Preferably, it is used for frequency-doubled light output of 1-2 micron laser.
[0032] According to the embodiment of the present invention, the nonlinear optical crystal can be used as an optical device in the ultraviolet-near infrared optical band.
[0033] According to an embodiment of the present invention, the nonlinear optical crystal is used in the fields of preparing a frequency doubling generator, an up or down frequency converter or an optical parametric oscillator.
[0034] Beneficial effects of the present invention:
[0035] The inventors found that in the nitrate system, π-conjugated (NO3) - The planar triangular groups have a wider band gap and a larger microscopic second-order polarizability, and their coplanar arrangement is conducive to the synthesis of nonlinear optical crystals with large band gaps and frequency doubling coefficients. (NO3) - The group is considered to be one of the excellent nonlinear optical active groups. In the sulfate system, (SO4) 2- The group is also a potential nonlinear optically active group and is often used to synthesize nonlinear optical crystals with a large band gap. Based on this, the present invention constructs a - and (SO4) 2-The compound of these two nonlinear optically active groups and the nonlinear optical crystal of the compound have the following specific characteristics:
[0036] (1) The present invention provides a novel nitric acid and sulfuric acid composite Bi8O6(OH)4(SO4)(NO3)6·H2O compound and its crystal. The Bi8O6(OH)4(SO4)(NO3)6·H2O crystal is crystallized in the non-centrosymmetric space group Pmn21, and its structure consists of a unique [Bi8O 10 (SO4)] blocks the polar cage and free [NO3] - The zero-dimensional crystal structure. (SO4) 2- The introduction of the group into the Bi-O cage forms a unique polar closed cage, and presents a polarization superposition enhancement effect, which makes the crystal have a strong frequency doubling effect and has the potential to be applied in the ultraviolet to near-infrared region. At the same time, the crystal does not absorb moisture, is stable in the air, and has good physical properties.
[0037] (2) The Bi8O6(OH)4(SO4)(NO3)6·H2O crystal of the present invention outputs a strong 532nm light under 1064nm laser irradiation, and its powder frequency doubling effect is about 12 times that of α-SiO2.
[0038] (3) The Bi8O6(OH)4(SO4)(NO3)6·H2O crystal of the present invention has a wide light transmittance range, and its ultraviolet absorption cutoff wavelength can reach 265nm. It can be applied to the ultraviolet-near infrared region and has potential application prospects in the fields of laser frequency conversion, electro-optical modulation, photorefractive information processing and information storage.
[0039] (4) The physical and chemical properties of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal of the present invention are stable.
[0040] (5) The preparation method of the Bi8O6(OH)4(SO4)(NO3)6·H2O compound and crystal of the present invention has a simple process, a fast growth rate and a low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the crystal structure of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal of the present invention.
[0042] Figure 2 The figure is a comparison diagram of the X-ray diffraction pattern obtained by fitting the crystal structure of Example 2 and the X-ray diffraction of the sample powder of Example 1.
[0043] Figure 3Schematic diagram of frequency doubling test, wherein 1 is a laser, 2 is an incident laser beam, 3 is the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal prepared in Example 3, 4 is the generated outgoing laser beam, and 5 is a photomultiplier tube equipped with a filter.
[0044] Figure 4 This is the frequency doubling test result of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2.
[0045] Figure 5 This is the UV-visible-near-infrared diffuse reflectance image of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2.
[0046] Figure 6 This is the infrared spectrum of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2. DETAILED DESCRIPTION
[0047] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0049] Example 1
[0050] Preparation of Bi8O6(OH)4(SO4)(NO3)6·H2O Compound
[0051] The Bi8O6(OH)4(SO4)(NO3)6·H2O compound was prepared by the following steps:
[0052] (a) Bi(NO3)3·5H2O (0.015 mol, 7.276 g), H2O (8 mL), and H2SO4 solution (0.1 ml, concentration 98%) were placed in a reactor with a polytetrafluoroethylene liner (25 mL), and the temperature was raised to 180°C at a rate of 20°C / h and kept constant for 2 days;
[0053] (b) After the reaction is completed, the system is naturally cooled to room temperature, and Bi8O6(OH)4(SO4)(NO3)6·H2O compound powder can be obtained after separation and drying.
[0054] Example 2
[0055] Preparation of Bi8O6(OH)4(SO4)(NO3)6·H2O Crystals
[0056] Bi8O6(OH)4(SO4)(NO3)6·H2O crystals were prepared by the following steps:
[0057] (a) Bi(NO3)3·5H2O (0.15 mol, 72.76 g), H2O (80 mL) and H2SO4 solution (1 ml, concentration 98%) were placed in a reactor with a polytetrafluoroethylene liner (250 mL), and the temperature was raised to 180°C at a rate of 15°C / h and crystallized at this temperature for 7 days;
[0058] (b) After the crystallization is completed, the reaction system is cooled to room temperature at a rate of 5°C / h. After separation and drying, Bi8O6(OH)4(SO4)(NO3)6·H2O crystals can be obtained.
[0059] The schematic diagram of the structure of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal prepared in this embodiment is shown in Figure 1 As shown, the crystal belongs to the orthorhombic system, the space group is Pmn21, and the unit cell parameters are α=β=γ=90°, z=8.
[0060] Example 3
[0061] Preparation of Bi8O6(OH)4(SO4)(NO3)6·H2O Crystals
[0062] Bi8O6(OH)4(SO4)(NO3)6·H2O crystals were prepared by the following steps:
[0063] (a) Bi(NO3)3·5H2O (0.015 mol, 7.276 g), H2O (8 mL) and H2SO4 solution (0.1 ml, concentration 98%) were placed in a reactor with a polytetrafluoroethylene liner (25 mL), and the temperature was raised to 200°C at a rate of 20°C / h and crystallized at this temperature for 10 days;
[0064] (b) After the crystallization is completed, the reaction system is naturally cooled to room temperature, and Bi8O6(OH)4(SO4)(NO3)6·H2O crystals can be obtained after separation and drying.
[0065] Example 4
[0066] Structural analysis and phase analysis of Bi8O6(OH)4(SO4)(NO3)6·H2O crystal
[0067] The structure of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal samples prepared in Examples 2-3 was analyzed by single crystal X-ray diffraction. The crystal structure of Bi8O6(OH)4(SO4)(NO3)6·H2O was analyzed by using a Bruker SMARTAPEXⅢCCD diffractometer with a single crystal X-ray diffraction device and Mo Kα radiation ( ) were recorded at 293(2)K with a scan mode of ω=2θ. The data were processed for absorption correction using the Multi-Scan method. The structure was solved using the SHELXTL package; the positions of heavy atoms were determined by the direct method, and the coordinates of the remaining atoms were obtained by the difference Fourier synthesis method; the F-based 2 The full matrix least square method was used to refine the coordinates of all atoms and the anisotropic thermal parameters. The single crystal X-ray diffraction results showed that the chemical formula of the crystals prepared in Examples 2 to 3 was Bi8O6(OH)4(SO4)(NO3)6·H2O.
[0068] The phase prepared in Example 1 was analyzed by powder X-ray diffraction. The powder X-ray diffraction (XRD) data of Bi8O6(OH)4(SO4)(NO3)6·H2O in the range of 5° to 80° (2θ) with a step width of 0.02° and a step length of 2s were collected on a SmartLab9KW powder X-ray diffractometer with Cu-Kα radiation. The powder X-ray diffraction spectra show that the diffraction peak positions of the samples in Examples 1 to 3 are basically the same. Figure 2 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure of Example 2 is basically consistent with the peak position and intensity of the X-ray diffraction pattern of the sample powder of Example 1. This shows that the Bi8O6(OH)4(SO4)(NO3)6·H2O single crystal prepared in Example 2 of the present invention is a single pure phase with high purity.
[0069] Example 5
[0070] Frequency doubling test experiment of Bi8O6(OH)4(SO4)(NO3)6·H2O crystal
[0071] The Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2 was subjected to a frequency doubling test experiment. Figure 3 As shown. The 1064nm laser emitted by Nd:YAG solid laser is used as the fundamental frequency light to irradiate the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal powder prepared in Example 2, and the generated double frequency light is detected by a photomultiplier tube, and the harmonic intensity is displayed by an oscilloscope. The specific method is as follows:
[0072] The particle sizes of the crystal samples to be tested are sieved into 45-58 μm, 58-75 μm, 75-106 μm, 106-150 μm, 150-250 μm and 250-355 μm using a standard sieve. Figure 3 At position 3 in the device shown, at room temperature, a Q-switched Nd:YAG laser is used as the input light source (i.e., laser 1), and the incident wavelength of the incident laser beam 2 is 1064nm. After the incident laser beam 2 passes through the crystal 3 of Example 2, the frequency-doubled signal of the outgoing laser beam 4 after passing through the filter 5 is tested respectively, and the variation trend of the frequency-doubled signal with the particle size is observed to determine whether phase matching can be achieved. Under the same test conditions, α-SiO2 is used as the reference for the double frequency test. The test results are shown in FIG. Figure 4 As shown in the figure, the results show that Bi8O6(OH)4(SO4)(NO3)6·H2O crystals (i.e. Figure 4 The powder frequency-doubling effect of BSNO) under 1064nm laser irradiation is about 12 times that of α-SiO2 under the same conditions.
[0073] Example 6
[0074] Spectral Performance Test of Bi8O6(OH)4(SO4)(NO3)6·H2O Crystal
[0075] Taking the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 1 as a representative, the ultraviolet diffuse reflectance spectrum test was carried out on the Shimadzu Solid Spec-3700DUV spectrophotometer. The Nicolet iS50 FT-IR spectrometer recorded the Bi8O6(OH)4(SO4)(NO3)6·H2O at 500-4000cm -1 Infrared spectrum within the range. In the diffuse reflection test, BaSO4 is used as a reference substrate for baseline test, and then the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2 is ground into powder and spread on BaSO4 for reflection spectrum test. Figure 5 and Figure 6 They are the UV-Vis-NIR diffuse reflectance diagram and infrared spectrum diagram of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal sample prepared in Example 2. The results in the diagram show that the Bi8O6(OH)4(SO4)(NO3)6·H2O prepared by the present invention has a wider light transmittance range, and its UV absorption cut-off wavelength can reach 265nm; further through UV spectrum conversion, it can be known that the band gap of the Bi8O6(OH)4(SO4)(NO3)6·H2O crystal prepared by the present invention is relatively large, about 4.09eV.
[0076] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A compound, characterized in that Its chemical formula is Bi8O6(OH)4(SO4)(NO3)6·H2O.
2. The method for preparing the compound according to claim 1, characterized in that: The method comprises: mixing a compound containing a Bi element, a compound containing an S element and a compound containing an N element, and performing a hydrothermal reaction to prepare the compound.
3. The method according to claim 2, characterized in that The compound containing Bi element is selected from at least one of Bi2O3, BiF3, Bi(NO3)3·5H2O and BiI3. Preferably, the compound containing the S element is selected from at least one of H2SO4, (NH4)2SO4, K2SO4 and CaSO4. Preferably, the compound containing the N element is selected from at least one of LiNO3, NaNO3, KNO3, Ba(NO3)2 and Bi(NO3)3·5H2O. Preferably, in the compound containing Bi element, the compound containing S element and the compound containing N element, the molar ratio of Bi, S and N is n(Bi):n(S):n(N)=(5-20):(1-2):(15-60). Preferably, the reaction temperature of the hydrothermal reaction is 160-220° C.; the reaction time of the hydrothermal reaction is 1-3 days.
4. A nonlinear optical crystal, characterized in that: The chemical structural formula of the crystal is Bi8O6(OH)4(SO4)(NO3)6·H2O as stated in claim 1, that is, the nonlinear optical crystal is Bi8O6(OH)4(SO4)(NO3)6·H2O crystal.
5. The nonlinear optical crystal according to claim 4, characterized in that: The nonlinear optical crystal belongs to the orthorhombic system, and the space group is Pmn21; the unit cell parameters are α=β=γ=90°, z=8.
6. The nonlinear optical crystal according to claim 4, characterized in that: The nonlinear optical crystal has no symmetry center.
7. The nonlinear optical crystal according to claim 4, characterized in that: The nonlinear optical crystal is composed of [Bi8O 10 (SO4)] blocks the polar cage and free [NO3] - A zero-dimensional crystal structure.
8. The method for preparing a nonlinear optical crystal according to any one of claims 4 to 7, characterized in that: The method comprises: mixing a compound containing a Bi element, a compound containing an S element, a compound containing an N element and a solvent, and then heating and crystallizing the mixture to obtain the nonlinear optical crystal.
9. The preparation method according to claim 8, characterized in that: The heating crystallization temperature is 160-240°C; And / or, the heating crystallization time is 5 to 15 days.
10. Use of the nonlinear optical crystal according to any one of claims 4 to 7 in an optical device. Preferably, it can be used in the fields of laser frequency conversion, electro-optic modulation, photorefractive information processing or information storage.
Citation Information
Patent Citations
Heterobimetal sulfate nonlinear optical crystal material as well as preparation method and application thereof
CN113235164A
Inorganic compound crystal as well as preparation method and application thereof
CN114197050A
Infrared photoelectric detector based on bismuth-oxygen-sulfur microflower array or bismuth-oxygen-sulfur nanoflowers and preparation method of infrared photoelectric detector
CN115020518A
Bismuth sulfide nanorod photocatalyst as well as preparation method and application thereof
CN116351437A
Potassium niobate compound, potassium niobate nonlinear optical / electro-optical crystal and preparation method and application of potassium niobate nonlinear optical / electro-optical crystal
CN117682559A